Mongolia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper describes economic developments in Mongolia during the 1990s. Real GDP grew by a robust 6 percent in 1995, but this success proved to be short lived. The sharp improvement in the terms of trade in 1995 boosted incomes and eased the financial constraints of the budget, enterprises, and banks. This enabled the government to delay price adjustments for electricity, heating, fuels, and key foods. Although measured inflation was cut from the 50-60 percent range in 1995 to less than 30 percent in mid-1996, the underlying inflation pressures remained.